Pengaruh Kualitas Pelayanan Terhadap Loyalitas Konsumen Pada Service Center Perusahaan Oppo Smartphone Di Surakarta - PUTRA, VAVANDA PRAHATAMA, Imronudin, SE, MSi, Ph.D (2017)
The purpose of this study was to determine the effect of service quality consists of variable; tangible, reliability, responsiveness, assurance, and empathy to customer loyalty in the Service Center OPPO Smartphone in Surakarta. This type of research is quantitative, with a population of customers at the Service Center OPPO Smartphone in Surakarta with a sample of 100 respondents. Decision convinience sampling technique using sampling techniques to the data model used the data crossection. Collecting data in this study using a questionnaire with Likert scale, and used are partially or assessment t test. Obtained results are variable responsive and empathy show the effect on loyalty service center OPPO while variable tanggible, reliability, and assurance no significant effect on loyalty OPPO service center. The test results obtained determination coefficient R Square of 61.9% and the remaining 38.1% is influenced by other factors beyond the variables studied.